Composition and Technological Properties of Modified Lingonberry (Vaccinium vitis-idaea L.) Pomace - Simona Šimkutė; Loreta Bašinskienė; Michail Syrpas; Dalia Čižeikienė (Applied Sciences)
Lingonberry pomace (LP) is a by-product rich in valuable bioactive compounds and can be used in the food industry after various treatments and property characterization. This study aimed to evaluate the impact of commercially available enzymes (Viscozyme® L, Pectinex® Ultra Tropical, and Celluclast® 1.5 L) and supercritical carbon dioxide (SFE-CO2) extraction technology on the chemical composition and technological properties of treated LP products. The Megazyme kit was used to determine the soluble dietary fiber (SDS) and insoluble dietary fiber (IDF) contents, while the changes in mono-, disaccharide, and oligosaccharides were analyzed by applying high-pressure liquid chromatography with a refractive index detector. The analyzed properties were as follows: the water swelling capacity (WSC), water retention capacity (WRC), water solubility index (WSI), oil retention capacity (ORC), bulk density (BD), and emulsion stability of modified LP. The tested LP contained 8.49 g/100 g of SDF and 65.36 g/100 g of IDF (in dry matter). The partial separation of lipophilic substances during SFE-CO2 extraction did not significantly affect the enzymatic hydrolysis efficiency. The amount of oligosaccharides in the LP increased using enzymes with pectinolytic activity (Viscozyme® L and Pectinex® Ultra Tropical), while cellulolytic enzymes (Celluclast® 1.5 L) increased the amount of SDF and improved the IDF/SDF ratio. Enzymatic hydrolysis increased the SI, WRC, and ORC of LP powder. Emulsions with LP hydrolyzed with Pectinex® Ultra Tropical demonstrated the highest stability during storage. This study demonstrates that the modification of LP powders provides diverse technological properties, which could expand the application of such products for further food production.